A perceptual socio-hydrological model of co-evolutionary coupled human–water system based on historical analysis, Mashhad basin, Iran. Issue 3 (17th February 2021) - Gholizadeh Sarabi, Shiva; Davary, Kamran; Ghahraman, Bijan; Shafiei, Mojtaba
ABSTRACT: Understanding how human and water systems co-evolve is a vital step towards achieving sustainability. This paper presents a historical socio-hydrological analysis of a semi-arid and overexploited basin in Eastern Iran, which is currently experiencing a serious water crisis. The co-evolutionary history of the socio-hydrological system within the basin was divided into three phases: natural, expansion and contraction. During the natural phase (from the Lower Paleolithic era to 650 AD), the basin was in pristine condition. In the expansion phase, including traditional development (650 to 1920) and industrial development (1920 to the present), the major proportion of non-renewable groundwater was employed towards economic gain. Considering the banning of groundwater development in the basin in 1966, the contraction phase has gradually begun since then; notwithstanding this, the expansion phase has continued. Furthermore, guided by historical analysis, a perceptual socio-hydrological model was developed to improve understanding of the co-evolutionary dynamics of the coupled human–water system.